Mimesis, (in)justiça e o direito como regulação da metamorfose: ensaio sobre a inveja no fenômeno jurídico - Guilherme, Thiago de Mello Azevedo (2022)
Contemporary society faces multiple challenges because of the popularization of internet and social movements, bringing difficulties to Law as an institution to play its role inside society and through connections with other powers – in case, legislative and executive. The very word ‘power’, enlightning the difficulty to coming into a concept, brings out questions that fragilizes current social organization, denouncing ancient roots to problems faced in contemporary times. Therefore, and having as a basis a historical panorama developed throughout the thesis, the main objective of this research is to analyze the envy problem and how this phenomenon is connected with a justice theory, shaping along the centuries what society understands by ‘fair’ and ‘unfair’. This context, obvious, regard to the very judiciary phenomenon, which is approached through the concepts of mimetic envy and sense of unfairness, besides other related feeling, such as indignation. In order to be possible to relate envy and Law, with all the perspectives involved, it is needed to bring authors such as Foucault, Rawls, Klein, Girard and Ferraz Junior, going through related subjects to make possible the comprehension about the way that envy influences the sense of fairness and unfairness – and how it occurred in many ways among history. We begin with Rawls’ Justice Theory to visualize how the author (doesn’t) include envy in his ideal of justice and, through questions and problems that comes from this lack of prevision, the research works with Aristotheles and others to see the advance of envy in history and the phenomenons that, when in contact with it, were able to shape envy and justice until the contemporary society – which still mirrors in its fellow men to constitute its individuals, but which demonstrates a high sense of injustice, especially in view of the most recent nuances related to the Judiciary. In view of the above, the objective of this thesis is to analyze all these phenomena to question, in addition to the relationship between envy and law what can be done in contemporary society to solve the incompleteness and incongruities that have been denounced by individuals through the internet – and, above all, the notion of envy itself